2016
DOI: 10.1038/nature20165
|View full text |Cite
|
Sign up to set email alerts
|

S-2-hydroxyglutarate regulates CD8+ T-lymphocyte fate

Abstract: R-2-hydroxyglutarate accumulates to millimolar levels in cancers with gain-of-function isocitrate dehydrogenase 1/2 mutations. These levels of R-2-hydroxyglutarate affect 2-oxoglutarate-dependent dioxygenases. Both R- and S-2-hydroxyglutarate, the other enantiomer of this metabolite, are detectible in healthy individuals, yet their physiological function remains elusive. Here we show that CD8+ T-lymphocytes accumulate 2-hydroxyglutarate in response to T-cell receptor triggering. This increases to millimolar le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
319
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(331 citation statements)
references
References 51 publications
11
319
0
1
Order By: Relevance
“…The extent to which larvae accumulate L-2HG is striking, as the only other healthy tissues known to accumulate high concentrations of L-2HG are T lymphocytes and cultured human cells that experience hypoxia (20,21). Since we raised larvae under normoxic conditions (Materials and Methods), our results suggested that larvae accumulate L-2HG via a novel metabolic mechanism.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The extent to which larvae accumulate L-2HG is striking, as the only other healthy tissues known to accumulate high concentrations of L-2HG are T lymphocytes and cultured human cells that experience hypoxia (20,21). Since we raised larvae under normoxic conditions (Materials and Methods), our results suggested that larvae accumulate L-2HG via a novel metabolic mechanism.…”
Section: Resultsmentioning
confidence: 82%
“…Discussion L-2HG was long considered a metabolic waste product, as eukaryotic genomes lack enzymes devoted to synthesizing this molecule, most cell types quickly degrade L-2HG, and L-2HG accumulation in humans is primarily associated with disease states (3, 12, 15). Recent studies, however, indicate that L-2HG can function as a metabolic signaling molecule and demonstrate a need to better understand the normal cellular functions of this compound (17,20,21). Our findings establish Drosophila as a model for studying L-2HG and provide a genetic framework for conducting in vivo studies of this putative oncometabolite.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…In the current issue of Nature, Tyrakis et al 6 report on the physiological role of S-2HG in T cells. T cells display a high degree of metabolic flexibility as their needs change during periods of rapid proliferation and cytolytic activity, and these metabolic changes are required for T-cell function and the formation of durable memory cell populations.…”
mentioning
confidence: 99%
“…I will always remember our last conversation; he came to my office to share his excitement over a new aspect of hypoxia, S-2-hydroxyglutarate, and how this affects cells in the immune system; a paper that was just recently published in Nature. 4 Lorenz will be missed by many friends and colleagues in Sweden and abroad.…”
mentioning
confidence: 99%